PRODUKTIVITAS ALAT EXCAVATOR VIBRO HAMMER UNTUK PEMANCANGAN SSP REUSE PADA PROYEK RENTANG IRRIGATION MODERNIZATION PROJECT DI KABUPATEN MAJALENGKA - Adinda Alfina Deswiyanti; Rijaluddin, Arief (Universitas Majalengka, 2024)
Rentang Dam is currently implementing a project, namely the Rentang Irrigation ModernizationProject (RIMP), which aims to restore irrigation functions, stabilize soil conditions, and alsooptimize water distribution. One of the projects that is being implemented as an effort to stabilize thecondition of the land is the installation of SSP Reuse piling. In the erection of SSP Reuse, the heavyequipment used was a vibro hammer excavator. From the erection of the SSP Reuse erection usinga vibro hammer excavator, its productivity can be seen. In this study, we review the productivity ofa vibro hammer excavator tool for erecting SSP Reuse on the right side of the CP. 168 – CP. 170110 meters long. The erection of the SSP Reuse is a follow-up effort to ensure that landslides do notoccur and access to residents' houses is wide. The productivity of the vibro hammer excavator forerecting SSP Reuse with a working day of 30 days per 8 hours, the average point obtained per dayis 9.17 sticks. Meanwhile, for the cycle time on day 1 at 13 SSP Reuse points with dimensions of 8 x0.4 m with vibration via a vibro hammer, the total cycle time was 200.71 minutes and the averagecycle was 15.44 minutes. Finally, the average cycle time of the vibro hammer piling tool taken during30 days of work had a cycle time of 11.33 minutes per rod.